ELECTROSPINNING PAN/PdCl2 NANOFIBER FOR HIDROGEN STORAGE – THE INFLUENCE OF THE PREPARATION METHOD - Rodrigues da Silva, Ana Neilde (2020)
The search for materials for hydrogen storage that are able to adsorb and desorb hydrogen molecules has received attention. Nanofibers have been studied because it has some interesting characteristics like high surface to volume ratio and the ease of producing by means of a low-cost setup. Polyacrylonitrile (PAN) has allowed the possibility of obtaining carbon nanofibers from the electrospinning process followed by a thermal treatment; moreover Pd has the capability of store hydrogen and can form a complex with dimethylformamide (DMF) so that, during the preparation of the solution of PAN and PdCl2, both present high solubility in the solvent.  Thus, the results demonstrated that as Pd can form complex with DMF the preparation method of the PAN+PdCl2 solutions influences the interaction between Pd and PAN. The decrease in dispersion viscosity and an unexpected increase in the diameter of the fibers confirm the hypothesis. The FTIRS and XPS analysis confirm that the Pd complexes with DMF by means of bonds to N.